Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Effects of amount of lactose in milk replacer on gastrointestinal function of dairy calves - R. Fukumori; T. Nakayama; M. Hirose; I. Norimura; K. Izumi; K. Shimada; H. Mineo; M.A. Steele; S. Gondaira; H. Higuchi; T. Watanabe; H. Ueda; et al. (Animal Feed Science and Technology, 2025)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Impact of Surfactants on the Performance of Clopidogrel-Copovidone Amorphous Solid Dispersions: Increased Drug Loading and Stabilization of Nanodroplets - Clara E. Correa Soto; Yi Gao; Anura S. Indulkar; Keisuke Ueda; Geoff G. Z. Zhang; Lynne S. Taylor (Pharmaceutical Research, 2022)

Correction to: Common findings of blaCTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2019)

Effects of Transcranial Direct Current Stimulation of the Posterior Parietal Cortex on the Control of Visual Attention - Y. Hirakawa; K. Takeda; S. Tanabe; S. Koyama; T. Ueda; K Morishima; M. Iwai; S. Kuno; I. Motoya; H. Sakurai; Y. Kanada (Neurophysiology, 2019)

Perovskite-type titanate zirconate as photocatalyst for textile wastewater treatment - A. M. Ferrari-Lima; A. C. Ueda; E. A. Bergamo; R. G. Marques; E. A. V. Ferri; C. S. Pinto; C. A. A. Pereira; P. H. Yassue-Cordeiro; R. P. Souza (Environmental Science and Pollution Research, 2017)

Common findings of bla CTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2017)

Characterization of a new anulavirus isolated from Amazon lily plants - S. Fuji; M. Kikuchi; S. Ueda; T. Toda; H. Furuya; F. Fukumoto; K. Hanada (Archives of Virology, 2013)

Genomic and serological detection of bat coronavirus from bats in the Philippines - Shumpei Tsuda; Shumpei Watanabe; Joseph S. Masangkay; Tetsuya Mizutani; Phillip Alviola; Naoya Ueda; Koichiro Iha; Satoshi Taniguchi; Hikaru Fujii; Kentaro Kato; Taisuke Horimoto; Shigeru Kyuwa; et al. (Archives of Virology, 2012)

Detection of a new bat gammaherpesvirus in the Philippines - Shumpei Watanabe; Naoya Ueda; Koichiro Iha; Joseph S. Masangkay; Hikaru Fujii; Phillip Alviola; Tetsuya Mizutani; Ken Maeda; Daisuke Yamane; Azab Walid; Kentaro Kato; Shigeru Kyuwa; et al. (Virus Genes, 2009)

In Vitro and In Vivo Release of Vascular Endothelial Growth Factor from Gelatin Microparticles and Biodegradable Composite Scaffolds - Zarana S. Patel; Hiroki Ueda; Masaya Yamamoto; Yasuhiko Tabata; Antonios G. Mikos (Pharmaceutical Research, 2008)

Unique grouping of the Far East Asian begomovirus complex based on sequence analyses of the DNA-A genome and associated DNAβ satellite molecules isolated from tomato, honeysuckle and Eupatorium plants in Japan - S. Ueda; M. Onuki; K. Hanada; Y. Takanami (Archives of Virology, 2008)

Collagen type I matrix affects molecular and cellular behavior of purified porcine dental follicle cells - S. Tsuchiya; M. J. Honda; Y. Shinohara; M. Saito; M. Ueda (Cell and Tissue Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Population Research of Genetic Polymorphism at Amino Acid Position 631 in Chicken Mx Protein with Differential Antiviral Activity - T. Seyama; J. H. Ko; M. Ohe; N. Sasaoka; A. Okada; H. Gomi; A. Yoneda; J. Ueda; M. Nishibori; S. Okamoto; Y. Maeda; T. Watanabe (Biochemical Genetics, 2006)

Molecular mechanisms involved in anti-inflammatory effects of proton pump inhibitors - O. Handa; N. Yoshida; N. Fujita; Y. Tanaka; M. Ueda; T. Takagi; S. Kokura; Y. Naito; T. Okanoue; T. Yoshikawa (Inflammation Research, 2006)

First report of the Q biotype ofBemisia tabaci in Japan by mitochondrial cytochrome oxidase I sequence analysis - S. Ueda; J. K. Brown (Phytoparasitica, 2006)

Complete nucleotide sequence of the genomic RNA of an Amami-O-shima strain of East Asian Passiflora potyvirus - H. Iwai; R. Terahara; Y. Yamashita; S. Ueda; M. Nakamura (Archives of Virology, 2006)

Roles of Aquaporin-3 Water Channels in Volume-Regulatory Water Flow in a Human Epithelial Cell Line - H. Kida; T. Miyoshi; K. Manabe; N. Takahashi; T. Konno; S. Ueda; T. Chiba; T. Shimizu; Y. Okada; S. Morishima (The Journal of Membrane Biology, 2005)

Elimination of chrysanthemum stunt viroid from an infected chrysanthemum cultivar by shoot regeneration from a leaf primordium-free shoot apical meristem dome attached to a root tip - M. Hosokawa; A. Otake; K. Ohishi; E. Ueda; T. Hayashi; S. Yazawa (Plant Cell Reports, 2004)

Merging of multiple signals regulating Δ9 fatty acid desaturase gene transcription in Saccharomyces cerevisiae - Y. Nakagawa; A. Ueda; Y. Kaneko; S. Harashima (Molecular Genetics and Genomics, 2003)

Development and disintegration of phragmoplasts in living cultured cells of a GFP?TUA6 transgenic Arabidopsis thaliana plant - K. Ueda; S. Sakaguchi; F. Kumagai; S. Hasezawa; H. Quader; U. Kristen (Protoplasma, 2003)

Application of odor-stimulated labeling methods of olfactory receptor neurons of sockeye salmon using agmatine - H. Iwase; S. Matsumoto; T. Shoji; H. Ueda (Fish Physiology and Biochemistry, 2003)

Changes in neurosteroid biosynthesis during sexual maturation of lacustrine sockeye salmon - S. Matsumoto; H. Yamada; M. Iwata; S. Adachi; K. Yamauchi; H. Ueda (Fish Physiology and Biochemistry, 2003)

Changes in GnRH levels in the brain and pituitary gland during migrations of sockeye salmon and chum salmon - T. Kitani; S. Matsumoto; H. Yamada; M. Amano; M. Iwata; H. Ueda (Fish Physiology and Biochemistry, 2003)

Detection of Japanese yam mosaic virus by RT-LAMP - S. Fukuta; T. Iida; Y. Mizukami; A. Ishida; J. Ueda; M. Kanbe; Y. Ishimoto (Archives of Virology, 2003)

Characteristics of a rice beer (zutho) and a yeast isolated from the fermented product in Nagaland, India - Y. Teramoto; S. Yoshida; S. Ueda (World Journal of Microbiology and Biotechnology, 2002)

General Utility of the Chicken βB1-Crystallin Promoter to Drive Protein Expression in Lens Fiber Cells of Transgenic Mice - Jennifer R. Taube; Chun Y. Gao; Yoji Ueda; Peggy S. Zelenka; Larry L. David; Melinda K. Duncan (Transgenic Research, 2002)

Second record of Cyclopina kiraensis , a small, brackish-water cyclopoid copepod, in Japan - H. Ueda; S. Ohtsuka; Y. Seike; S. Ohtani (Limnology, 2001)

Metabolism of 2-Nitrofluorene, an Environmental Pollutant, and 2-Acetylaminofluorene in Fish - O. Ueda; S. Kitamura; Y. Huruse; T. Saito; Y. Kanzaki; Y. Yano; K. Tatsumi; S. Ohta (Bulletin of Environmental Contamination and Toxicology, 2001)

Investigation of physicochemical form of uranium in sediment of brackish Lake Obuchi using sequential extraction procedure - S. Ueda; H. Hasegawa; T. Iyogi; H. Kawabata; K. Kondo (Limnology, 2000)

Microtubule-dependent migration of the cell nucleus toward a future leading edge in amoebae ofPhysarum polycephalum - M. Ueda; T. Kuroiwa; S. Matsunaga; S. Ogihara (Protoplasma, 2000)

Simplified song in an island population of the bush warbler Cettia diphone - S. Hamao; K. Ueda (Journal of Ethology, 2000)

Characteristics of fluctuations in salinity and water quality in brackish Lake Obuchi - S. Ueda; H. Kawabata; H. Hasegawa; K. Kondo (Limnology, 2000)

Intramolecular Stable Isotope Ratios of N 2 O in the Tropical Swamp Forest in Thailand - N. Boontanon; S. Ueda; P. Kanatharana; E. Wada (The Science of Nature, 2000)

Interannual, seasonal, local and body size variations in reproduction of the prawn Penaeus ( Marsupenaeus ) japonicus (Crustacea: Decapoda: Penaeidae) in the Ariake Sea and Tachibana Bay, Japan - M. Minagawa; S. Yasumoto; T. Ariyoshi; T. Umemoto; T. Ueda (Marine Biology, 2000)

”In vivo cryotechnique" in combination with replica immunoelectron microscopy for caveolin in smooth muscle cells - I. Takayama; N. Terada; T. Baba; H. Ueda; Y. Kato; Y. Fujii; S. Ohno (Histochemistry and Cell Biology, 1999)

Allelic diversity at class II DRB1 and DQB loci of the pig MHC ( SLA ) - T. Hosokawa Kanai; Y. Tanioka; M. Tanigawa; Y. Matsumoto; S. Ueda; T. Onodera; Y. Matsumoto (Immunogenetics, 1999)

Analysis of 5′-upstream non-coding region of FI-carboxymethyl cellulase gene from Aspergillus aculeatus - T. Ooi; K. Morotomi; S. Kinoshita; J. Honda; S. Ueda; M. Arai (Biotechnology Letters, 1999)

Geographical variations in the trophic structure of the plankton community along a eutrophic–mesotrophic–oligotrophic transect - S. Uye; N. Iwamoto; T. Ueda; H. Tamaki; K. Nakahira (Fisheries Oceanography, 1999)
The geographical variations in trophic structure of the plankton community, as defined by total and relative carbon biomass of phytoplankton (PP), bacteria (BA), heterotrophic nanoflagellates (HNF), microzooplankton (MZ), and herbivorous (HNZ) and carnivorous net‐zooplankton (CNZ), were investigated along an inshore–offshore transect from the innermost part of Osaka Bay to the Pacific Ocean off Kii Channel, Japan, in June 1991. Based on physico‐chemical properties of the water and topographical features, the transect was divided into three trophic areas, i.e. eutrophic, mesotrophic and oligotrophic ones. The average carbon biomass of the total plankton community was highest (438 mg m −3 ) in the inshore eutrophic area, and declined steeply offshore (141 and 26.6 mg m −3 in the mesotrophic and oligotrophic areas, respectively). In the offshore oligotrophic area, the relative biomass of BA to PP and the relative biomass of small heterotrophs (i.e. BA, HNF and MZ) to the total heterotrophs were higher than in the other areas, indicating that the microbial food chain predominated. In the mesotrophic area, the biomass of HNZ (primarily copepods) was conspicuously high, even higher than that of PP, suggesting that the traditional grazing food chain prevailed. Because of this short food chain, a productive fishing ground is formed there. In the eutrophic area, the biomass of HNZ was much smaller relative to the enormous biomass of PP, indicating that a considerable amount of primary production was not utilized directly by the metazoan zooplankton. However, the relative contribution of the small heterotrophs to the total heterotrophs’ biomass was higher in this area, as in the oligotrophic area.

Slight difference in primary amino acid sequence of p17 matrix protein of HIV-1 exerts profound influence on its antigenicity - K. Taniguchi; H. Tsuchie; S. Kageyama; M. Iwasaki; T. Takagi; F. Sasao; S. Ueda; T. Kurimura (Archives of Virology, 1998)

Correlation among dominance status, metabolic rate and otolith size in masu salmon - T. Yamamoto; H. Ueda; S. Higashi (Journal of Fish Biology, 1998)
In spatial competition between individuals, neither fish sex nor body mass affected dominance status in masu salmon Oncorhynchus masou . In contrast, resting metabolic rate ( M R ) was significantly correlated with dominance status, indicating that a high metabolic rate can increase the dominance rank of juvenile salmon. Whole animal growth rate was significantly correlated with M R , but not with initial body weight. This suggests that the body size of masu salmon is not a cause, but rather a consequence, of dominance status which is closely related to M R . The increment width between otolith daily rings was also significantly correlated with M R . Thus, the size of the Otolith may indicate the degree of M R .

Uptake of 26-Al and 67-Ga into brain and other tissues of normal and hypotransferrinaemic mice - Aleksandar Radunovic´; Fukiko Ueda; Kishor B. Raja; Robert J. Simpson; Jill Templar; Samantha J. King; John S. Lilley; J. Philip Day; Michael W.B. Bradbury (BioMetals, 1997)

Naturally occurring dual infection with human and bovine rotaviruses as suggested by the recovery of G1P8 and G1P5 rotaviruses from a single patient - O. Nakagomi; Y. Isegawa; R. L. Ward; D. R. Knowlton; E. Kaga; T. Nakagomi; S. Ueda (Archives of Virology, 1994)

Rapid detection of African horsesickness virus by the reverse transcriptase polymerase chain reaction (RT-PCR) using the amplimer for segment 3 (VP3 gene) - K. Sakamoto; R. Punyahotra; N. Mizukoshi; S. Ueda; H. Imagawa; T. Sugiura; M. Kamada; A. Fukusho (Archives of Virology, 1994)

A new typing method for the avian infectious bronchitis virus using polymerase chain reaction and restriction enzyme fragment length polymorphism - Z. Lin; A. Kato; Y. Kudou; S. Ueda (Archives of Virology, 1991)

Typing of recent infectious bronchitis virus isolates causing nephritis in chicken - Z. Lin; A. Kato; Y. Kudou; K. Umeda; S. Ueda (Archives of Virology, 1991)

Generation and characterization of the human immunodeficiency virus type 1 mutants - A. Adachi; N. Ono; H. Sakai; K. Ogawa; R. Shibata; T. Kiyomasu; H. Masuike; S. Ueda (Archives of Virology, 1991)

Cross-reactivity among cowpox, ectromelia and vaccinia viruses with monoclonal antibodies recognizing distinct antigenic determinants in A-type inclusion bodies - N. Kitamoto; S. Tanimoto; K. Hiroi; H. Miyamoto; N. Wakamiya; S. Ueda; S. Kato (Archives of Virology, 1986)

Polypeptide analysis with monoclonal antibodies of A type inclusion bodies induced by cowpox virus - N. Kitamoto; S. Tanimoto; K. Hiroi; T. Tanaka; H. Miyamoto; N. Wakamiya; K. Ikuta; S. Ueda; S. Kato (Archives of Virology, 1986)

Studies on the serological cross-reaction between Marek's disease virus and herpesvirus of turkeys using monoclonal antibodies to major virus-specific polypeptides - K. Ikuta; K. Nakajima; S. Ueda; S. Kato; K. Hirai (Archives of Virology, 1984)

Cross-reactivity between cowpox and vaccinia viruses with monoclonal antibodies - N. Kitamoto; E. Goto; S. Tanimoto; T. Tanaka; H. Miyamoto; N. Wakamiya; K. Ikuta; S. Ueda; S. Kato (Archives of Virology, 1984)

Temperature-sensitive virion transcriptase activity in mutants of WSN influenza virus - S. L. Mowshowitz; M. Ueda (Archives of Virology, 1976)